AUTOMATED DEVICE FOR ICE SURFACE QUALITY ASSESSMENT - M. V. Davydov; P. A. Belous (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
Results of ice quality assessment depending on various conditions of the environment and ice preparation are presented in article. The optimum indicators of the studied values influencing the ice surface quality are revealed. It is possible to estimate ice speed qualities objectively with the device, that imitates skater sliding. The purpose of the study is to determine the dependence of the sliding friction coefficient on the parameters of water treatment, the conditions for freezing the ice surface, the temperature of the ice surface, hardness and other parameters. The imitation is the movement of the mobile platform mounted on skates, supplied with the module transferring to the personal computer the values of skates sliding on the ice surface friction parameters. To measure the distance traveled by the device, the laser ranging method was used. The efficiency of the developed device and the technique of its application for assessment of ice quality on sports arenas are shown. The dependences of the quality of the ice surface on the surface temperature of the ice, air temperature, temperature of the poured water are considered. Accounting of these indicators during competitions allows to create «fast» ice for high sports results demonstration. The best values of the range of the device were recorded with the following parameters: ice surface temperature – from –3,5 to –4,5 °С, concrete slab temperature – –6 °С, ice thickness – 27–29 mm, filled water temperature – 50–55 °С, cutting the top layer of ice with an ice-filling machine – 100 %. The worst values of the range of the device were obtained with the following parameters: ice surface temperature – from –5,3 to –5,4 °С, filled water temperature – 30–35 °С, the top layer of ice was not cutby an ice-filling machine.